Identifikasi Risiko Keluhan Musculoskeletal Disorders Menggunakan Nordic Body Map pada Pekerja Jasa Percetakan di Kecamatan Tawang Kota Tasikmalaya - Nazmi, Tiara Nurul; Risma Puspita; Siti Markhamah; Nova Ayu Gumilang; Adinda Aulia (JOURNAL SAINS STUDENT RESEARCH, 2026)
Occupational health evaluations in the informal printing service sector, which has high physical demands and static postures, are still minimally conducted. The research aims to determine the risk level of Musculoskeletal Disorders (MSDs) complaints among printing service workers in Tawang District, Tasikmalaya City. This study used an observational analytical design with a cross-sectional approach. The sample was 32 respondents from printing service workers. The sampling technique used accidental sampling. The research instrument used the Nordic Body Map (NBM) questionnaire to map the location and severity of muscle pain. The data were analyzed quantitatively based on NBM scoring. The results showed that the majority of respondents worked beyond normal time limits with an average of 12 hours per day. The risk level of musculoskeletal complaints was mostly low for 29 respondents (90.6%), and moderate for 3 respondents (9.4%). Although the current complaint level is classified as low, extreme working hours and static sitting postures create a latent injury threat. Ergonomic work positions and regular stretching are highly necessary to minimize the risk of long-term musculoskeletal injuries.